Characteristics of different lipid droplet-mitochondrial contacts patterns during lipid droplet metabolism in T2DM-induced MASLD - Ye Xu; Yuan Zhang; Wen Sun; Qiang Tang; Wanyu Feng; Hongjian Xiao; Jingjie Wang; Xinmeng Yuan; Mengqi Xiang; Yaran Gao; Hanyu Zhang; Jiao Lu (Scientific Reports)
Abstract Mitochondrial function is crucial for hepatic lipid metabolism. Current research identifies two types of mitochondria based on their contact with lipid droplets: peridroplet mitochondria (PDM) and cytoplasmic mitochondria (CM). This work aimed to investigate the alterations of CM and PDM in metabolic dysfunction-associated steatotic liver disease (MASLD) induced by spontaneous type-2 diabetes mellitus (T2DM) in db/db mice. It was found that insulin resistance increased both the number and size of lipid droplets in the liver by enhancing the accumulation of free fatty acids, which is accompanied by an increase in contacts with mitochondria. We described the different patterns of tight contacts between small lipid droplets and mitochondria in purified CM and PDM by examining their oxidation states and morphological characteristics. In CM, enhanced fatty acid oxidation resulted in elongated mitochondria that surrounded single small lipid droplets and were responsible for lipid droplet consumption, while in PDM, increased substrates for lipid synthesis promoted lipid droplet expansion with the assistance of the endoplasmic reticulum. These data show the different ways in which mitochondrial contact with lipid droplets could provide new insights for future research on liver lipid metabolism.